Innovative Character Education: Building the Golden Generation of 2045 Through Holistic Moral Education - Muhammad Haris; Hidayatul Mufidah (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
This study explores innovative approaches to character education aimed at developing Indonesia's Golden Generation of 2045. As the nation approaches its centennial of independence, preparing youth with strong moral foundations and character becomes increasingly critical amid rapid technological and social changes. This qualitative descriptive research employs a library research approach to analyze current character education frameworks, identify challenges, and propose holistic innovations that integrate traditional values with modern pedagogical approaches. The findings reveal that effective character education requires a multi-dimensional approach combining family involvement, technology integration, culturally responsive teaching, and experiential learning. The study proposes a comprehensive framework for character education that addresses cognitive, affective, and behavioral dimensions while respecting Indonesia's cultural diversity. This research contributes to the ongoing discourse on character development and provides practical recommendations for educational stakeholders seeking to nurture morally sound, globally competitive citizens for Indonesia's second century of independence.